GE_GERICHTE A/4400/2015 vom 29. August 2016 - GE Cour de justice (2016)
AVIS; ENLEVE; ECRCOM; REPLIQ; PROTRA; SAISIE; DESIGN; INSAIS; MOYNOU; MINVIT | Recours au TF interjeté le 22 juin 2016 par le débiteur, rejeté par arrêt du 29 août 2016 ( | LP.92.1.3; LP.93.1; LP.96.1